Distribution strategies for the base of the pyramid: an exploratory study in Brazil - Barki, Edgard Elie Roger (2010)
Access has been one of the main difficulties companies have faced in emerging markets (PRAHALAD, 2005). The capillarity of the market, the existence of small, not professionalized and sometimes informal retailers, the lack of infrastructure and high transportation costs are some of the distribution challenges companies face in poorer regions. The literature concerning the Base of the Pyramid (BoP) is still recent and only after the seminal article by Prahalad and Hart (2002), it evolved into many different management perspectives. However, there is a lack of researches concerning distribution strategies to the BoP. Therefore, the main objective of this research is to identify, in the perception of executives working in the market, the conditions associated to a satisfactory distribution for the BoP market in Brazil and to build a substantive theory that helps to shed light to the understanding of the distribution phenomenon adopted by consumer goods companies to reach the BoP market in Brazil. In order to accomplish the objectives of this thesis, a grounded theory methodology (Glaser; Strauss, 1967; Corbin; Strauss, 2008) was used. This approach helped to identify the channel strategies used by local and global companies in the market. Many techniques for data collection were applied. The most important one was in-depth interviews with 26 executives from 24 different consumer goods companies in Brazil. Among the companies there were small, medium and large enterprises; which were also grouped as manufacturers, distributors and retailers. Furthermore, secondary data were examined to identify business strategies to reach BoP and map global distribution initiatives. A database from a consumer panel was also used to analyze what and where BoP consumers purchase non-durable goods. It was verified that small and traditional retailing is a very strong format in BoP markets and in the Northern/Northeastern regions. Cash & Carry is a format that is growing a lot. On the other hand, hypermarkets are not very used by low income population. The results suggest that three major categories are associated to a satisfactory distribution: (a) willingness, which means the effort, knowledge and enthusiasm a firm has to operate at BoP markets; (b) well-done execution, which is related to designing correctly the marketing channel and operating efficiently in an environment full of obstacles, such as lack of infrastructure, capillarity, lack of safety, regional differences and informality, and (c) relationship, which was perceived to be friendlier and essential at BoP markets, since it is very difficult for manufacturers to reach the entire market alone. It is more likely to have a satisfactory distribution when manufacturers establish strong relationships in the marketing channel. Besides, small retailers have a perception of isolation and expect a higher level of relationship. These major categories explain also the competitive advantage that local companies have in relation to MNCs and large companies. Despite of the limitations of an exploratory study, it is expected that this thesis will contribute to the BoP knowledge as well as to the identification of the peculiarities of distribution in BoP markets.